THE INFLUENCE OF LEARNING CULTURE AND STUDENT PERSONALITY CHARACTERISTICS ON LEARNING SATISFACTION THROUGH ONLINE LEARNING READINESS AS A MEDIATION VARIABLE FOR STUDENTS OF THE FACULTY OF ECONOMICS, STATE UNIVERSITY OF JAKARTA - Sulistyowati, Yuyun; Febriantina, Susan; Faslah, Roni (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to determine the influence of learning culture, student personality characteristics, readiness to learn boldly on learning satisfaction. The research was conducted for 7 (seven) months starting from December 2020 to June 2021. The research method was quantitative with the type of research that was explanatory. The sample used in this study found 198 respondents from the education students of the Faculty of Economics, State University of Jakarta. The data collection technique used a proportional random technique. The data analysis technique used SmartPLS software version 3.0 PLS (Partial Least Square) with structural equation analysis (SEM). The results showed that each variable had a significant effect.